Jual Beli Kosmetik Mengandung Lanolin dari Domba yang Tidak Disembelih Menurut Hukum Islam - Tamara Natalia , Astrid; Khoiruddin; Yusika Sumanto (Jurnal Iqtisad, 2025)
The development of the modern cosmetics industry has raised issues regarding the halal status of the raw materials used, with lanolin being one of the most controversial ingredients. The problem arises when lanolin is obtained from sheep that have been slaughtered in an unclear manner. This study aims to analyze the halal status of lanolin from sheep that have not been slaughtered by looking at the views of evaluating its compliance with halal regulations in Indonesia. This study uses a qualitative method with a library research and comparative analysis approach to examine the opinions of scholars and halal regulations in Indonesia. Data collection techniques were carried out through documentation methods, namely searching through fiqh books, fatwas from the Indonesian Ulema Council (MUI), scientific journals, the Halal Product Guarantee Law, and other relevant academic literature. The results of the study show that the majority of scholars from various schools of thought argue that lanolin is a pure and halal substance because it comes from sheep's wool, which is not considered carrion, and has undergone a process of transformation to become halal and pure because it has been changed into another form. This view is reinforced by the MUI fatwa, which states that lanolin from halal animals that have not been slaughtered may be used in non-food products such as cosmetics. According to Islamic law, the sale and purchase of cosmetics containing lanolin is considered valid and halal, as long as it fulfills the conditions and requirements of buying and selling.